2019
DOI: 10.1111/aos.14327
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐session repeatability of quantitative metrics using widefield optical coherence tomography angiography (OCTA) in elderly subjects

Abstract: Purpose To assess the repeatability of retinal vascular metrics using different postprocessing methods as obtained from the swept‐source optical coherence tomography angiography ( SS ‐ OCTA ). Methods Thirty‐two participants (63% males; mean [ SD ] age, 70 [7] years) underwent SS ‐ OCTA imaging ( PLEX ® … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 39 publications
(83 reference statements)
2
24
0
Order By: Relevance
“…Moghimi and coworkers 8 reported fewer measurable steps from a healthy mean value to a modeled residual floor for OCT-A vascular measures, suggesting that the larger dynamic range of vascular measures was offset by increased measurement variability. Although OCT-A has been demonstrated to have good repeatability in both and normal and diseased eyes, 49 , 50 other studies have shown that OCT-A measurements can be affected by signal strength 51 and choice of vascular processing approach, 52 as well as physiological characteristics, 53 among other factors. Given these potential sources of variability, these factors should be considered in a progression study, where it may also be advantageous to include baseline parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Moghimi and coworkers 8 reported fewer measurable steps from a healthy mean value to a modeled residual floor for OCT-A vascular measures, suggesting that the larger dynamic range of vascular measures was offset by increased measurement variability. Although OCT-A has been demonstrated to have good repeatability in both and normal and diseased eyes, 49 , 50 other studies have shown that OCT-A measurements can be affected by signal strength 51 and choice of vascular processing approach, 52 as well as physiological characteristics, 53 among other factors. Given these potential sources of variability, these factors should be considered in a progression study, where it may also be advantageous to include baseline parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Second, different hardware and scanning protocols can result in a difference in the OCTA metrics, such as scanning speed, lateral resolution, numbers of A-scan and B-scan. We have shown that using different filters can generate perfusion density, ranging from 29.8 to 45.1% in a 3 × 3 mm 2 macula scan 31 . Therefore, OCTA metrics are not comparable without considering these factors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, there is no consensus on which filter and which parameters are optimal for extracting the OCTA metrics. We have shown previously high perfusion density reproducibility using frangi filter 31 , and the parameters were tuned so that the binarized perfusion map has highest similarity to anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…OCTA imaging was performed with a prototype SS-OCT instrument (Plex Elite 9000, Carl Zeiss Meditec, USA), which employs a wavelength swept source and detects the interference signal by a photodetector. 4 The light source has a central wavelength at 1050 nm with a scanning rate of 100 000 A-scans per second. The axial and lateral resolutions in tissue are 6.3 µm and 20 µm, respectively.…”
Section: Methodsmentioning
confidence: 99%